HUBUNGAN ANTARA MOTIVASI KERJA DENGAN KOMITMEN TERHADAP ORGANISASI GURU GUGUS II KECAMATAN CIPAYUNG DEPOK - Nur Hikmah (Universitas Pakuan, 2020)
RELATIONSHIP BETWEEN MOTIVATION WITH ORGANIZATIONAL COMMITMENTThis research is classified into a correlational research which consists of one independent variable, Motivation (X) with one dependent variable, Organization Commitment (Y). The hypothesis of the research is: There is a positive correlation between motivation and organization commitment. This research was conducted in Cipayung, Depok, West Java, Indonesia. The population of 104 teacher, and randomly selected as sample 82 teachers. The method of collecting research data in the field uses the survey method while the statistical method of data analysis uses correlation analysis techniques, simple regression analysis. Hypothesis measurement is taken both at the significance level α = 0.05 and at the significance level α = 0.01. Based on the calculation results, the research results are obtained: there is a very significant positive relationship between Motivation with organization commitment with the regression equation that is Ŷ = 96.16 + 0.36X, the correlation coefficient (ry) of 0.411, and the coefficient of determination (ry2) of 0.169 or 16.9. Based on the above calculation results, it can be concluded that motivation can be increased through organization commitment